Short- and Long-Term Renal Outcome of Hemolytic-Uremic Syndrome in Childhood - Vaterodt, Laura; Holle, Johannes; Hüseman, Dieter; Müller, Dominik; Thumfart, Julia (Frontiers in Pediatrics, 2018)
Introduction Hemolytic-uremic syndrome (HUS) is a common cause for intrarenal acute kidney injury in childhood. More than 90% of HUS cases are associated with an infection by Shigatoxin-producing E. coli (STEC) whereas the reminder comprises a heterogeneous group (here classified as Non-STEC-HUS). Renal impairment can persist in patients with HUS. This study presents data from four decades investigating the short- and long-term outcome of HUS in childhood. Materials and Methods In a retrospective single-center-study clinical and laboratory data of the acute phase and of 1- to 10-year follow-up visits of children with HUS were analyzed. Results 92 HUS-patients were identified from 1996 to 2014 (STEC-HUS-group: n = 76; Non-STEC-HUS-group: n = 16) and 220 HUS-patients between 1976 and 1995. STEC-HUS was increasingly caused by Non-O157 strains and mortality rate declined over the past decades (1.3 versus 9.5%). Renal sequelae persisted more often in the group 1976-1995 (39.3%) than in the group 1996-2014 (28.3%), but more than 50% of all patients were lost to follow-up. Conclusion Although renal outcome has improved over the investigated last decades, patients with HUS still face a high risk of permanent renal damage. These findings underline the importance of a consequent long-term follow-up in HUS-patients.